2014
DOI: 10.1002/app.41586
|View full text |Cite
|
Sign up to set email alerts
|

Lauric acid coated fly ash as a reinforcement in recycled polymer matrix composites

Abstract: Sustainable composites were developed from fly ash (FA) and recycled polypropylene (R) with lauric acid (LA) as the coupling agent. The FA particles were surface-coated with 1, 2, 3, and 5 wt % LA, and the coating on the FA particles was verified by transmission electron microscopy and Fourier transform infrared spectroscopy. R and LA-coated FA particles were melt-mixed in a 1:1 weight ratio to achieve a high-filler-loaded composite. The flexural, impact, nanoindentation, and fracture surface analyses were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The peak at 1416 cm −1 indicated the presence of -OH groups. The peak at 3643 cm −1 was attributed to -OH absorption bands, suggesting the presence of Ca(OH) 2 in treated fly ash (Sengupta et al 2015). In case of immobilized bacterial cells, similar band stretching as the previous two was found which may be indicated that the bacterial cells immobilized on fly ash by physical entrapment.…”
Section: Fourier-transform-infrared (Ftir) Spectroscopysupporting
confidence: 77%
“…The peak at 1416 cm −1 indicated the presence of -OH groups. The peak at 3643 cm −1 was attributed to -OH absorption bands, suggesting the presence of Ca(OH) 2 in treated fly ash (Sengupta et al 2015). In case of immobilized bacterial cells, similar band stretching as the previous two was found which may be indicated that the bacterial cells immobilized on fly ash by physical entrapment.…”
Section: Fourier-transform-infrared (Ftir) Spectroscopysupporting
confidence: 77%
“…Furthermore, a composite from fly ash (FA) and recycled polypropylene (R) were developed using LA as a coupling agent. Nanoindentation tests results also demonstrated an increase in the mechanical properties in the case of the 1 and 2 wt % LA-coated composites in comparison to the uncoated counterpart (Sengupta et al 2015).…”
Section: Mechanical Properties Of Cht/ss 3d Scaffoldsmentioning
confidence: 79%
“…As with other fillers, FA is surface modified with coupling agents due to weak interfacial bonding between the FA particles and polymer matrix. Green couplings agents, stearic acid [217], lauric acid [218], and palmitic acid [219], were shown to be effective coupling agents in rPP/FA composites. The use of green coupling agents instead of conventional chemicals can improve the sustainability and reduce the cost of rPO/FA composites.…”
Section: Production Of Composites From Rpos and Inorganic/organic Fillersmentioning
confidence: 99%